Magnetic and magnetocaloric property studies on nanoparticles of electron-doped manganites R0.15Ca0.85MnO3 (R = Pr and Nd). (5th June 2019) - Das, Sandip; Kavipriya, T; Nirmala, R
Abstract: Magnetic and magnetocaloric properties of two electron-doped manganite nanoparticles namely Pr0.15 Ca0.85 MnO3 and Nd0.15 Ca0.85 MnO3 are studied. The samples were prepared by sol-gel method and characterized by powder x-ray diffraction and scanning and transmission electron microscopy. Both bulk and nanoparticles crystallize in orthorhombic structure at room temperature. The crystallite size varies between 30 to 85 nm. While the bulk Pr0.15 Ca0.85 MnO3 and Nd0.15 Ca0.85 MnO3 order antiferromagnetically at 147 K and 112 K (TN ), their nano-counterparts of size 83 nm and 89 nm show antiferromagnetic cusp around 133 K and 130 K respectively, with larger magnetization values below TN in 5 kOe field. The field dependent magnetization data at 5 K also show this enhancement with decrease in particle size for Nd0.15 Ca0.85 MnO3 nanoparticles and this difference is attributed to the surface moments. The isothermal magnetic entropy change (ΔSm ) shows a peak value of about +0.53 Jkg −1 K −1 and −0.28 Jkg −1 K −1 for 70 kOe field change near TN respectively, for the 83 nm size Pr0.15 Ca0.85 MnO3 and 32 nm size Nd0.15 Ca0.85 MnO3 samples. The occurrence of inverse magnetocaloric effect for larger size sample suggests dominant antiferromagnetic character while the normal magnetocaloric effect in small size particles is in accordance with dominant ferromagnetism. However, the isothermal magnetic entropy change values are about one order smaller in the nanoparticles underlining the role of long-range order in magnetocaloric effect of such materials.